Covid-19 waste facemask conundrum: A facile way of utilization through fabricating composite material with unsaturated polyester resin and evaluation of its mechanical properties. Issue 12 (December 2022) - Bin Mobarak, Mashrafi; Hossain, Md. Sahadat; Chowdhury, Fariha; Ahmed, Samina
Abstract: Since the outbreak of novel coronavirus (COVID-19), the use of personal protective equipment (PPE) has increased profusely. Among all the PPEs, face masks are the most picked ones by the mass people for protective purpose. This spawned extensive daily use of face masks and production of masks had to augment to keep up this booming demand. Such extensive use of face masks has resulted in a huge waste generation. Lack of proper disposal, waste management and waste recycling have already led this waste to pervade in the environment. In quest of finding a solution, here in this research, a composite material was fabricated utilizing waste face mask (WFM) with unsaturated polyester resin (UPR) and the mechanical properties were evaluated. The composites were fabricated by incorporating 1%, 2%, 3%, 4% and 5% WFM (by weight) within the UPR matrix in the shredded form following hand lay-up technique. Tensile properties, i.e., tensile strength (TS), tensile modulus (TM) and percentage elongation at break (% EB) as well as flexural properties, i.e., bending strength (BS) and bending modulus (BM) were evaluated for the fabricated composites. According to the results obtained, the 2% WFM loaded composites showed highest values of TS, TM, BS and BM which are 31.61 N/mm 2, 1551.41 N/mm 2, 66.53 N/mm 2 and 4632.71 N/mm 2 respectively. These values of 2% WFM loaded composite are 69.58%, 107.78%, 129.49% and 152% higher than the values of the control sample (UPR). Such results depict the successfulness of WFM's incorporation as a reinforcing material in the composite materials. Attenuated Total Reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), scanning electron microscopy (SEM), water uptake and thickness swelling tests were also carried out for the fabricated composites. FTIR of the collected WFM revealed the fiber to be of polypropylene and the existing functional groups were also identified. The SEM images confirmed the proper adhesion of WFM and UPR in terms of mechanical bonding rather than chemical bonding. Water absorption and dimension change was investigated by water uptake and thickness swelling test. To sum up, the way we have utilized WFM as a reinforcing agent in a composite material, this could be a possible solution for the face mask's waste conundrum. Graphical abstract: Image 1 Abstract : COVID-19 pandemic; Face mask waste; Composite material; Hand lay-up technique; Mechanical properties.